Seeding Public Goods Is Essential for Maintaining Cooperation in Pseudomonas aeruginosa - Loarca, Daniel; Díaz, Dánae; Quezada, Héctor; Guzmán-Ortiz, Ana Laura; Rebollar-Ruiz, Abril; Presas, Ana María Fernández; Ramírez-Peris, Jimena; Franco-Cendejas, Rafael; Maeda, Toshinari; Wood, Thomas K.; García-Contreras, Rodolfo (Frontiers in Microbiology, 2019)
Quorum sensing in P. aeruginosa controls the production of costly public goods such as exoproteases. This cooperative behavior is susceptible to social cheating by mutants that do not invest in the exoprotease production but assimilate the amino acids and peptides derived by the hydrolysis of proteins in the extracellular media. In sequential cultures with protein as the sole carbon source, these social cheaters are readily selected and often reach equilibrium with the exoprotease producers. Nevertheless, an excess of cheaters causes the collapse of population growth. In this work, using the reference strain PA14 and a clinical isolate from a burn patient, we demonstrate that the initial amount of public goods (exoprotease) that comes with the inoculum in each sequential culture is essential for maintaining population growth and that eliminating the exprotease in the inoculum leads to rapid population collapse. Therefore, our results suggest that sequential washes should be combined with public good inhibitors to more effectively combat P. aeruginosa infections.